Biochemival Characterization of an Antibactrial Glycoprotein from Achatina fulica ferussac Snail Mucus Local Isolate and Their Implication on Bacterial Dental Infection - Berniyanti, Titiek; Waskito, Edy Bagus; s, Suwarno (Indonesian Journal of Biotechnology, 2007)
Snails crawl over a variety of potentially contaminated surfaces and their foot is the primary site of entry forpathogens, parasites and a range of opportunistic organisms, so it is a little wonder that they must have a defensivesystem to protect them. The mucus secreted on the body surfaces of mollusks is known to play crucial role inlocomotion, feeding, osmoregulation, reproduction and protection of epithelial surfaces. The snail mucus alsocontains Glycoaminoglycans (GAGs) which are complex polysaccharides that participate in the regulation ofphysiological processes through the interactions with a wide variety of proteins. GAGs, such as heparin, serve as keyto biological response modifiers, in example for acting asa a target for pathogen and parasitic factors for attachment,invasion, and immune system.For years, it has been known that the mucus secretions from snails Achatina fulica ferussac local isolate can be usedas a medication, and even empirically it is used to treat infected teeth tahat is suffered by people in rural area. Theantibacterial factor was surveyed in the aqueous extract and the mucin fraction of snail Achatina fulica ferussac, andthey exhibited positive antibacterial for Gram-positive, Escherichia coli and Gram negative, Streptococcus mutans. Inthe following study, it has been proved that an antibacterial content in the mucus was a Glycoprotein. It wascomposed of two subunits of Molecular Weight (MW) 71-73 kDa. The GelCode Glycoprotein Staining Kit detectedglycoprotein sugar moieties in polyacrylamide gel and on nitrocellulose membrane, while the glycoproteincarbohydrate estimation kit detected glycoprotein and estimated carbohydrate content. The glycoprotein contentwas 4.537 ± 0.876 for carbohydrate and 6.420 ± 1.242 for protein.Keywords : characterization, glycoprotein, Achatina fullica Ferussac snail mucus, galur Jawa, antibacterialfactor